Encountering Others through Graphic Narrative. Layers of Empathy in Hanneriina Moisseinen’s "The Isthmus" - Aura Nikkilä; Anna Vuorinne (Widok. The Foundation for Visual Culture, 2022)
In this article we analyze Hanneriina Moisseinen’s historical comic The Isthmus with in the framework of empathy. By focusing on the role of multimodal storytelling – the combination of drawings, text, and photographs – we explore the ways in which The Isthmus invites the reader to empathize with the marginalized others of the past, both human and non-human. We propose that empathy should be understood as a multidimensional phenomenon of imagination, feeling, and understanding. To discuss how Moisseinen’s comic elicits empathy, we apply Elisa Aaltola’s theory of varieties of empathy, which provides a nuanced account for understanding how living beings relate to and understand each other. We argue that comics storytelling has the possibility not only of fostering the reader’s capacity to imagine the lives of others, but also to invite them to attend to the experiences of others through affect, embodiment, and reflection.